Posverity: the pinoch return - Flores Morales, Jorge Alberto (2019)
The post-truth presents us with the banalization of the events or objective facts, in favor of positions and particular interests appealing to the emotions and indignation of the people where the truth and the lie coexist accepting both equally. In this perspective, the truth turns out to be an interpretation of reality or an alternative reality among others, which is conducive to manipulate people or social groups according to particular interests far from reality and the truth of events.